Ageing and long term care in Singapore. - Cheah, Chin Han. (2008)
The study attempts to provide a solution to finance the care services of the elderly population. The study also examines the ageing experiences of selected countries to provide a more comprehensive understanding of the ageing process. This is crucial as Singapore will face the problem of an ageing population soon and must learn to cope with it.